Toleransi Fungisida sebagai Determinan Kompatibilitas Pengendalian Hayati: Studi dari Streptomyces xiangtanensis NBSP3F dan Trichoderma asperellum G-4274-1: Fungicide Tolerance as a Determinant of Biocontrol Compatibility: Insights from Streptomyces xiangtanensis Strain NBSP3F and Trichoderma asperellum Strain G-4274-1 - Iskandar, Mhd Fiqry; Izzati, Salwa; Khairunnisa, Puti; Rinaldi, James; Saputra, Nanda; Ramadhan, Muhammad Hafizt; Albana, Hasan (DINAMIKA PERTANIAN, 2026)
Background: The intensive and prolonged use of synthetic fungicides, particularly mancozeb, exerts selective pressure on non-target microbial communities, potentially promoting the emergence of tolerant populations. Therefore, biocontrol agents that remain effective under such chemical stress are needed. Objective: This study aimed to evaluate the tolerance responses of Streptomyces xiangtanensis NBSP3F and Trichoderma asperellum G-4274-1 to mancozeb exposure across a gradient of concentrations. Methods: The experiment was conducted in vitro using a poisoned food technique at six concentrations (0%, 1%, 2%, 3%, 4%, and 5%) with six replications. Tolerance of S. xiangtanensis was assessed qualitatively based on colony growth, while T. asperellum was quantitatively evaluated using mycelial radial growth and growth inhibition metrics. Results: Results showed a concentration-dependent suppression of growth in both isolates. S. xiangtanensis maintained complete growth (100%) at 0–1% concentrations, decreased to 75% at 2–3%, 50% at 4%, and 25% at 5%. T. asperellum exhibited stable growth (90–100%) at 0–2%, moderate reduction (70–72.5%) at 3–4%, and a decline to 45% at 5%. Comparatively, T. asperellum showed higher physiological resilience than S. xiangtanensis under intermediate to high fungicide stress, though both isolates had reduced adaptability at the highest concentration. Conclusions: These findings indicate species-specific differences in adaptive capacity to multisite fungicidal stress, likely due to variation in metabolic flexibility and stress-response mechanisms. Collectively, both isolates demonstrate strong potential as multifunctional biocontrol agents, integrating pathogen suppression, plant growth promotion, and possible roles in pesticide-tolerant biodegradation, offering promising implications for sustainable agroecosystem management.